2020
DOI: 10.21203/rs.3.rs-54215/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuum of Hepatitis C Care Cascade in Prison and Following Release in the Direct-acting Antivirals Era

Abstract: Background People with criminal justice involvement contribute remarkably to the rising hepatitis C virus (HCV) burden; however, the continuum of care is a major barrier to prison-based programs. We aimed to evaluate a comprehensive HCV care model in an Iranian provincial prison. Methods Between 2017–2018, in the Karaj Central Prison, newly admitted male inmates received HCV antibody testing and venipuncture for RNA testing (antibody-positive only). Participants with positive RNA underwent direct-acting anti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The high success rate of 98.8% found in our study correlates well with previously reported results. 5,7,2628…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high success rate of 98.8% found in our study correlates well with previously reported results. 5,7,2628…”
Section: Discussionmentioning
confidence: 99%
“…The high success rate of 98.8% found in our study correlates well with previously reported results. 5,7,[26][27][28] Several factors have been reported to be associated with achieving higher SVR rates in prisoners. In the era of interferon-based therapy, these included younger age, better pretreatment liver fibrosis status, HCV genotype other than 1, and lower baseline viral load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation